Leadership Management Strategies of the Principal in Improving the Quality of Educators and Educational Personnel at SMP Negeri 3 Lhoknga: A Literature Review - darlisna ubbg; rahmattullah; kausar (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This literature review aims to delve into the leadership management strategies that school principals utilize to enhance the quality of performance among educators and educational personnel at SMP Negeri 3 Lhoknga. In recent years, the role of school leadership has gained increasing recognition for its pivotal influence on educational outcomes. Effective leadership not only shapes the school’s vision and culture but also fosters an environment conducive to professional growth and positive student learning experiences. This review synthesizes a variety of empirical studies and theoretical frameworks, highlighting key leadership styles such as transformational leadership, which inspires and motivates staff through a shared vision, and distributed leadership, which encourages collaboration and responsibility among team members. These leadership approaches have been shown to significantly impact teacher satisfaction, commitment, and ultimately, student achievement. In the context of SMP Negeri 3 Lhoknga, several specific strategies have been identified as effective in enhancing educator performance. These include the implementation of tailored professional development programs that address the unique needs of the teaching staff, fostering a culture of peer collaboration through mentorship and co-teaching initiatives, and establishing robust performance appraisal systems that provide constructive feedback and opportunities for growth. Additionally, this review examines the socio-cultural and institutional challenges that school leaders face in their quest to improve educational quality. These can include resistance to change among staff, limited resources, and external pressures from education policies. By analyzing case studies from both local and international contexts, the review aims to draw conclusions about best practices and transferable strategies that can be adopted not only by SMP Negeri 3 Lhoknga but also by other educational institutions facing similar challenges.